Thirty years of rice‐crab coculture in China—Research progress and prospects - Jie Bao; Hongbo Jiang; Xiaodong Li (Reviews in Aquaculture, 2022)
Chinese mitten crab ( Eriocheir sinensis ) culture in rice paddy fields is a representative model of integrated agriculture‐aquaculture systems developed in China over the last 30 years. The economic and ecological benefits of rice‐crab coculture are significantly improved compared to those of rice monoculture. Under coculture conditions, rice provides shelter for crabs and improves the aquatic environment, while crabs eliminate pests and weeds, reduce the need for chemical fertilizers and pesticides, and stabilize rice production. At the same time, rice‐crab coculture helps protect biodiversity and reduce greenhouse gas emissions. An in‐depth study has led to the significant development of rice‐crab coculture technology in China and has established ecological breeding models with regional characteristics. These studies have established breeding industry standards for paddy field engineering, stocking mode, water quality control, rice management, feeding, pest control and breeding management. However, more research is needed to standardize rice field engineering specifications, optimize coculture modes, clarify crab nutritional needs, develop disease prevention and control methods, elucidate the operational mechanism of rice‐crab coculture and ascertain energy‐material exchange with the external environment. Eventually, rice‐crab coculture can be highly integrated to utilize the fewest resources while providing the greatest economic and environmental benefits. This review provides a theoretical reference for further research in the field of rice‐crab coculture, examining aspects such as development history, economic benefits, organisms in the system (rice, crabs, plankton, zoobenthos, weeds and microorganisms), internal and external environmental benefits, and the direction of future development.